An Analysis of Guest Occupancy and Profit of Private and Public Hotels in Cox’s Bazar - Chowdhury, Thufathun Nessa; Chowdhury, MD. Mohiuddin (Asian Business Review, 2014)
Purpose: The aim of this research was to find out the differences in guest occupancies and profits of the private and public hotels between and within the years 2008 and 2014. Methodology: The researchers followed explanatory research to differentiate the data with statistical tools. The researchers undertook the deductive approach to test the hypothesis comparing occupancy and profit of the hotels. The researchers used survey and interview method in this study. Public and private hotels were chosen as sample during the year 2008 and 2014 from Cox’s Bazar main beach area. The samples were selected based on judgment sampling method. The researchers used mono method and a cross-sectional research by considering the data of the years 2008 and 2014 only. This research mainly based on field survey instead of depending on the artificial figures provided by the hotel officials. The information was confirmed by several respondents during the interview. Findings: Significant differences found in the occupancies and profits of the public and private hotels during the year 2008 and 2014 individually. Also, between the years, 2008 and 2014, differences were observed in occupancy and profit of the private hotels. No difference diagnosed in the occupancy and profit of public hotels between 2008 and 2014. In the survey, the researchers’ diagnosed that the hotels had a common tendency to avoid Tax payment to keep the profit uncut. Practical implications: Further research can be done to compare the tax earnings of the government from public and private sector at different period. New researchers can use this research data in further research to calculate the tax payment based on revenue earnings and occupancy. JEL codes: L40, M20